VD_FINDINFO Jug / 2024 / 498 vom 11. Juni 2024 - VD Tribunal cantonal (2024)
PROCÉDURE ÉCRITE, DÉTENTION ILLICITE, INTERDICTION DES TRAITEMENTS INHUMAINS | 3 CEDH, 10 Cst., 406 al. 1 let. a CPP (CH), 406 al. 1 let. d CPP (CH)